Orang Tua Sebagai Pendidik Dalam Perspertif Abdullah Nasih Ulwan - Parina, Parina; Handrianto, Budi; Al Hamat, Anung (Tawazun: Jurnal Pendidikan Islam, 2021)
The purpose of this study was to determine Abdullah Nasih Ulwan's view or perspective on parents as educators. The research method used is a qualitative research method with the type of literature review. The data or materials needed to complete this research come from the library in the form of books, encyclopedias, dictionaries, journals, documents, magazines and so on. What is meant by literature review research is that researchers study the thoughts of Abdullah Nasih Ulwan from a book he wrote Tarbiyatul Aulad on Child Education in Islam. According to Abdullah Nasih Ulwan, the parents in charge and the main educators for their children, so that educators are not only teachers at school. Allah has prepared parents as primary educators by instilling feelings or main capital as educators, such as affection, love and so on. The negligence of parents in educating their children will have fatal consequences for their children so that they cannot carry out their duties in future life as servants of Allah and khalifatulloh. Therefore, as primary educators, parents must understand the responsibilities, methods and principles of children's education. Abstrak Tujuan penelitian ini untuk mengetahui pandangan atau perpsektif Abdullah Nasih Ulwan tentang orang tua sebagai pendidik. Metode penelitian yang digunakan adalah metode penelitian kualitatif dengan jenis kajian pustaka. Data – data atau bahan-bahan yang diperlukan dalam menyelesaikan penelitian ini berasal dari perpustakaan baik berupa buku, ensklopedi, kamus, jurnal, dokumen, majalah dan lain sebagainya. Yang dimaksud dengan penelitian kajian pustaka yaitu peneliti mempelajari buku Tarbiyatul Aulad Pendidikan Anak dalam Islam yang ditulis oleh Abdullah Nasih Ulwan. Menurut Abdullah Nasih Ulwan orang tua penangungjawab dan pendidik utama bagi anak – anaknya, sehingga pendidik bukan hanya guru yang ada disekolah. Alloh sudah menyiapkan orang tua sebagai pendidik utama dengan menanamkan perasaan atau modal utama sebagai pendidik, seperti kasih sayang, cinta dan sebagainya. Kelalaian orang tua dalam mendidik anaknya akan berakibat fatal kepada anaknya sehingga tidak bisa melaksanakan tugas kehidupannya kelak sebagai hamba Alloh dan khalifatulloh. Oleh karena itu sebagai pendidik utama orang tua harus memahami tanggungjawab, metode dan kaidah-kaidah dalam pendidikan anak.